Examining accounting students' satisfactions on lecturers competencies and their performance in UiTM Terengganu / Yusliena Yusoff ... [et al.] - Yusoff, Yusliena; Tahar, Emiza; Abdul Aziz, Inayah; Che Ali, Merani; Jusoh, Rohayati; Ghazali, Rosliza (2020)
This study aims at examining the students' satisfaction in the Faculty of Accountancy, University Technology MARA, Terengganu. Students' satisfaction is an important element for all institutions of higher learning in order to attract students for enrolment and failure to meet the students' satisfaction will definitely affect the university's reputation and students' intake in future. Prior research have stated that students' satisfaction is related to lecturers' competencies and students' performance. Students' satisfaction may also have a crucial impact on their perception towards an institution, and thus, may affect the academic performance of students. Conceptually, students' satisfaction is an important marketing concept for higher education institutions and as the main stakeholders, satisfaction by students can be a sensitive issue. Generally, students' satisfaction can be contributed by various factors such as their grades, relationship with lecturers, lectures' expertise, learning environment, and classroom facilities. As such, students' satisfaction is not only crucial for supporting life at the university, but it can also boost the university's reputation. Thus, this study is examining the relationship between students' satisfaction and students' performance and also their satisfaction on lecturers' competencies while studying in UiTM Terengganu. Therefore, the objectives of this study are to examine the relationship between students' satisfaction with lecturers' competencies and their own performance. The students of the Faculty of Accountancy are selected as respondents in this research. For this purpose, the methodology that has been applied in this study is the quantitative method by using adapted questionnaires distributed to all students of the Faculty of Accountancy, UiTM Terengganu. The responses have been collected from the total population of 330 students from Diploma and Bachelor Degree of Accountancy for the semester September 2019 - January 2020. The analyses have been conducted by using the Statistical Package for Social Sciences (SPSS) 23. The findings of the study have revealed that both lecturers' competencies and students' performance have a positive relationship with students' satisfaction.